An essay: build your own from the ground up / Eugene Fregetto - Fregetto, Eugene (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
Which teaching method is best? The answer to this question depends upon whom, what, and when you are teaching; it also depends on where you want to begin a nascent entrepreneur's education: start with business basics or opportunity recognition? The approach recommended in this paper supports the development of rural entrepreneurship by providing an answer for the initial type of entrepreneurship program for people beyond the reach of an urban university. This essay presents an active and personalized approach to learning four essential competencies nascent entrepreneurs need in order to launch their first venture as well as any subsequent ventures; forsaking the passive learning approach wherein teachers lecture while students listen, read textbooks, and complete assignments. The four competencies are imagination, creativity, innovations, and entrepreneurial aspirations; essential competencies for the development of any viable business enterprise. The curriculum can be delivered solely as an online course or blended with the support of a team and facilitator as the "Build Your Own from the Ground Up" curriculum engages students to practice the techniques, skills, and competences required to tap their imagination and to mold the best ideas into the beginning of a via business enterprise.